Hak Waris Anak yang Lahir Dari Perkawinan Beda Agama Menurut Hukum Adat Bali - I Ketut Sukadana (Fakultas Hukum, Universitas Warmadewa, 2020)
The life of indigenous peoples in Indonesia with their diverse religions and cultures, does not rule out the possibility of cross-marriages between them, such as many marriages between people of different faiths. Marriage between people of different religions, in the community often causes problems in the family and even leads to divorce. The formulation of the problem in this paper is how is the legal status of interfaith marriages according to Law Number. 1 of 1974 and how the inheritance rights for children born from marriages of different religions according to Balinese customary law. This research is a normative legal research by examining the laws and regulations and using literature studies. The results showed that interfaith marriages in the Marriage Law in Indonesia were not strictly regulated in Marriage Law Number 1 of 1974 concerning Marriage in conjunction with Law Number 16 of 2019 concerning Amendments to the Marriage Law Number 1 of 1974 concerning Marriage. Marriage Law requires couples of different religions if they want to have a marriage, they must submit themselves to the religion of one party. As for the inheritance rights of children born from marriages of different religious partners according to Balinese customary law, if the child follows his father's religion then he will be given the right to inherit. However, if the child follows his mother's religion, he will not get the right to inherit. This is based on that the Balinese traditional inheritance law adheres to the principle of kapurusa (father line) and inheritance not only in the form of rights but also always attaches certain obligations that can only be carried out by heirs of the same religion as the heirs.